An Exploration of Oral-Gut Pathogens Mediating Immune Escape of Pancreatic Cancer via miR-21/PTEN Axis - Li, Rui; Hu, Yaoyuan; Hou, Shuhong (Frontiers in Microbiology, 2022)
Oral-gut pathogens are closely associated with pancreatic cancer, such as Campylobacter jejuni, Clostridium difficile, Enterococcus faecalis, Escherichia coli, Fusobacterium nucleatum, Helicobacter pylori, Porphyromonas gingivalis, and Vibrio cholera, but the related mechanisms remain not well understood. Phosphatase and tensin homolog (PTEN, a widely known tumor suppressor) play a key role in the anti-cancer immune system. Pancreatic cancer cells with PTEN loss are often in the immunosuppressive tumor microenvironment regulated by myeloid-derived suppressor cells (MDSCs), regulatory T cells (Tregs), and M2 macrophages, which are regarded as the mechanism in the immune escape of cancers. The miR-21, as an oncogene in human cancers, plays an important role in pancreatic cancer progression, downregulates the levels of PTEN, and may promote cancer to evade host immune surveillance. Some oral-gut pathogens have been found to promote miR-21 expression and reduce PTEN expression. On the other hand, most gut pathogens infection is thought to produce reactive oxygen species (ROS) or activate inflammatory cytokines, which may also induce ROS-mediated miR-21 expression. These pathogens' infection is involved with the cell density of MDSCs, Tregs, and M2 macrophages. Therefore, it is quite reasonable to propose that oral-gut pathogens possibly promote pancreatic cancer escaping from host immune surveillance by activating the miR-21/PTEN axis and immune-suppressive cells. The present exploration suggests that an increased understanding of the pattern of the effects of gut pathogens on the miR-21/PTEN axis will lead to better insights into the specific mechanisms associated with the immune escape of pancreatic cancer caused by oral-gut microbiota.